Venous thromboembolism prevention guidelines for medical inpatients: Mind the (implementation) Gap. Issue 10 (27th August 2013) - Maynard, Greg; Jenkins, Ian H.; Merli, Geno J.
<x xml:space="preserve">Abstract</x> BACKGROUND Hospital‐associated nonsurgical venous thromboembolism (VTE) is an important problem addressed by new guidelines from the American College of Physicians (ACP) and American College of Chest Physicians (AT9). METHODS Narrative review and critique. RESULTS Both guidelines discount asymptomatic VTE outcomes and caution against overprophylaxis, but have different methodologies and estimates of risk/benefit. Guideline complexity and lack of consensus on VTE risk assessment contribute to an implementation gap. Methods to estimate prophylaxis benefit have significant limitations because major trials included mostly screening‐detected events. AT9 relies on a single Italian cohort study to conclude that those with a Padua score ≥4 have a very high VTE risk, whereas patients with a score <4 (60% of patients) have a very small risk. However, the cohort population has less comorbidity than US inpatients, and over 1% of patients with a score of 3 suffered pulmonary emboli. The ACP guideline does not endorse any risk‐assessment model. AT9 includes the Padua model and Caprini point‐based system for nonsurgical inpatients and surgical inpatients, respectively, but there is no evidence they are more effective than simpler risk‐assessment models. CONCLUSIONS New VTE prevention guidelines provide varied guidance on important issues including risk assessment. If Padua is used, a threshold of 3, as well as 4, should be considered. Simpler VTE risk‐assessment models may be superior to complicated point‐based models in environments without sophisticated clinical decision support. Journal of Hospital Medicine 2013;8:582–588. © 2013 Society of Hospital Medicine